Hubungan Tingkat Pengetahuan Ibu Tentang Gizi Dengan Status Gizi Pada Batita Di Desa Sangge Kecamatan Klego Kabupaten Boyolali - Sufyanto, Rizal; , Endang Nur W, SST., M.Si Med (2016)
Introduction: The nutritional knowledge of mothers play a role in eating behaviors and variation of foods that are provided on the toddler's mother. The toddler who doesn't get a good meal intake will affect the nutritional status is lacking. Objective: to know the level of knowledge of nutrition in the mother who has the toddler nutrition status in the village of Klego sub-district of Sangge Boyolali Regency. Research methods: The research is obcervational with cross-sectional approach. The technique of sampling analysis using total sampling. Data is analyzed by Chi-Square test. Results: based on the distribution of mother's level of knowledge about nutrition data shows that the toddler's mother had more that level of knowledge the mother category is quite as much as 21 respondents (52.5%), based on the nutritional status of the distribution of the toddler shows data that most respondents with the toddler normal nutritional status as much as 31 respondents (77.5%) value pvalue of 0.001. Conclusion: there is a significant relationship between maternal nutrition knowledge level about nutrition against nutritional status on the toddler.